Optimizing the Urea Granule Size by Taguchi Approach - Mohamad, Norhidayah.; Shaaban, A. (International Journal of Engineering and Technology, 2018)
Urea granule fertilizer was produced by using lab scale fluidized bed granulator through the wet granulation process. This experiment was conducted to determine a dominant factor of few parameters used in producing urea granule. The Taguchi method was utilized to address these three factors which later were analyzed by using Analysis of Variance (ANOVA). The obtained results were analyzed by Signal-to-Noise ratio and ANOVA. Based on the Signal-to-Noise ratio analysis, indicates that spraying rate and viscosity are insignificance in determining the output. The mass of starch is the significant factor. The ANOVA results reveal the cassava starch contribute major influences on urea granule size formation, meanwhile spraying rate was indicated as minor contributor.Â Â Â